Applying semantic web and big data techniques to construct a balance model referring to stakeholders of tourism intangible cultural heritage. (2016) - Shi, Meiyu; Zhu, Wei; Yang, Hongji; Li, Chen
The development of tourism intangible cultural heritage, by its very nature, is a process of social construction by stakeholders through their transaction, coordination, interest alienation and sharing the responsibility. Coordinating and balancing the interest conflict within every stakeholder to achieve the 'Pareto Optimality' is a major difficulty in the tourism intangible cultural heritage development. In another side, semantic web is a computer term that is known its efficiency in knowledge representation of concepts. In this paper, we applied semantic web to modelling the balance model of stakeholders of tourism intangible heritage in the data collecting process, including data acquisition from entire network combining with structural equation method and path analysis based on a big data platform and questionnaire design, which is the innovative attempt to integrate these two typical computer technologies into social scientific research. Further analysis of the final constructed model demonstrates the effectiveness of the proposed application.